Determination of the moduli of elasticity and rupture, and energy consumption of the oil palm trunk (2007)
The moduli of elasticity and rupture, and the energy to cause failure under impact load of the oil palm trunk were determined. Samples for testing were obtained from the base, middle and top of the tree trunk. They were taken from both the core and outer regions of the trunk and tested under wet and dry conditions. The samples obtained from the outer layer of the base, and tested under dry conditions, gave the highest modulus of elasticity of 4,943N/mm2 and a modulus of rupture of 42.8N/mm2. The samples obtained from the inner section of the top and tested under wet conditions gave the lowest values of 369.7N/mm2 for modulus of elasticity and 0.4N/mm2 for modulus of rupture. The maximum value of energy consumption of 12.86 joules was recorded for the outer base section tested under wet conditions as against the minimum value of 0.45 joules recorded for the samples from the inner portion of the top and tested under dry conditions. There were a general decrease from the base to the top for the three parameters and from inside to outer section.